Implementasi Program Senam Kreasi untuk Meningkatkan Aktivitas Fisik Siswa SMK Arinda Palembang - Nurrahma, Fani; Triansyah, Deni; Sukmawati, Noviria; Fikri, Afrizal (Universitas Negeri Gorontalo, 2025)
The low level of physical activity among vocational high school students has become an increasing concern, particularly due to sedentary lifestyles and the intensive use of digital devices in daily activities. This community service program was implemented through a teaching assistance activity at SMK Arinda Palembang with the aim of improving students’ physical activity levels, movement coordination, and motivation to engage in regular physical exercise. The program was conducted over a two-month period, from October to November 2025, involving Grade X and XI students. A participatory-practice approach was applied, consisting of an initial observation of students’ physical activity conditions, delivery of basic physical fitness material, demonstration and practice of creative gymnastics, and evaluation based on observation. The creative gymnastics program included Senam Anak Indonesia Hebat, Poco-Poco, and Maumere, each session lasting approximately 30 minutes. The results indicated an increase in students’ active participation and enthusiasm, improved ability to maintain movement intensity throughout the sessions, enhanced coordination and rhythmic accuracy, and more positive attitudes toward physical activity. In addition, the program contributed to reducing sedentary behavior within the school environment. This creative gymnastics program serves as a simple, enjoyable, and sustainable alternative to support the integration of regular physical activity into school routines.